2021
DOI: 10.5194/mr-2021-40
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid Scan Electron Paramagnetic Resonance using an EPR-on-a-Chip Sensor

Abstract: Abstract. Electron paramagnetic resonance (EPR) spectroscopy is the method of choice to investigate and quantify paramagnetic species in many scientific fields, including materials science and the life sciences. Common EPR spectrometers use electromagnets and microwave (MW) resonators, limiting their application to dedicated lab environments. Here, we present an improved design of a miniaturized EPR spectrometer implemented on a silicon microchip (EPR-on-a-chip, EPRoC). In place of a microwave resonator, EPRoC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Arguably the smallest-scale implementation of Overhauser DNP to date has made use of a single-chip CMOS EPR spectrometer [102]. It has been shown that the circuitry required for EPR spectroscopy can be integrated into a single, high-field compatible complementary metal-oxide semiconductor (CMOS) chip [138][139][140]. Such integrated EPR spectrometers are extremely compact, with chip sizes of only a few millimeters, and can be operated with low power requirements.…”
Section: Overhauser Dynamic Nuclear Polarizationmentioning
confidence: 99%
“…Arguably the smallest-scale implementation of Overhauser DNP to date has made use of a single-chip CMOS EPR spectrometer [102]. It has been shown that the circuitry required for EPR spectroscopy can be integrated into a single, high-field compatible complementary metal-oxide semiconductor (CMOS) chip [138][139][140]. Such integrated EPR spectrometers are extremely compact, with chip sizes of only a few millimeters, and can be operated with low power requirements.…”
Section: Overhauser Dynamic Nuclear Polarizationmentioning
confidence: 99%
“…Arguably the smallest-scale implementation of Overhauser DNP to date has made use of a single-chip CMOS EPR spectrometer [102]. It has been shown that the circuitry required for EPR spectroscopy can be integrated into a single, high-field compatible complementary metal-oxide semiconductor (CMOS) chip [138][139][140]. Such integrated EPR spectrometers are extremely compact, with chip sizes of only a few millimeters, and can be operated with low power requirements.…”
Section: Overhauser Dynamic Nuclear Polarizationmentioning
confidence: 99%